Formulation and Optimization of Expandable Gastroretentive Tablet of Diltiazem Hydrochloride using Factorial Design - Shinde, Anilkumar J. (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: An attempt has been made to improve drug concentration in the stomach by preparing gastroretentive, swellable, matrix-based sustained release tablets of diltiazem hydrochloride that due to their size would be retained in the upper part of gastrointestinal tract. Materials and Methods: A 32 full factorial design was employed for the formulation of expandable tablets; two variables were evaluated. In the present investigation, the amounts of HPMC K100M and sodium carboxymethyl cellulose were selected as independent variables and effect of these variables, on swelling index (SI) and drug release was studied. Tablets were prepared and characterized by physical properties of compressed tablets such as hardness, friability, weight variation, content uniformity, SI, and drug release were determined. Results and Discussion: The SI of optimized batch varied between 114.21% and 220.41%. The percentage drug release of optimized batch was 15.60 at 1 h and 71.97% at 12 h. From the drug release kinetic study, Peppas model was found to be the best fit. Infrared spectrum and differential scanning calorimetric thermograms showed that there was no interaction between drug and polymers in the formulation. Expandable gastroretentive tablets were achieved a size more than the diameter of the pylorus and are not able to pass through the pylorus, thus causing prolongation of gastric residence time. Conclusion: The study indicates that development of diltiazem hydrochloride tablet can be beneficial in the treatment of hypertension. It releases drug in sustained manner for an extended period of time to reduce frequency of administration and improve patient compliance.